Genetic Consequences of Acute/Chronic Gamma and Carbon Ion Irradiation of Arabidopsis thaliana - Hase, Yoshihiro; Satoh, Katsuya; Seito, Hajime; Oono, Yutaka (Frontiers in Plant Science, 2020)
Gamma rays are the most frequently used ionizing radiation in plant mutagenesis; however, few studies are available on the characteristics of mutations at a genome-wide level. Here, we quantitatively and qualitatively characterized the mutations induced by acute/chronic gamma ray irradiation in Arabidopsis. The data were then compared with those previously obtained for carbon ion irradiation. In the acute irradiation of dry seeds at the same effective survival dose, gamma rays and carbon ions differed substantially, with the former inducing a significantly greater number of total mutation events, while the number of gene-affecting mutation events did not differ between the treatments. This may result from the gamma rays predominantly inducing single-base substitutions, while carbon ions frequently induced deletions ≥ 2 bp. Mutation accumulation lines prepared by chronic gamma irradiation with 100–500 mGy/h in five successive generations showed higher mutation frequencies per dose compared with acute irradiation of dry seeds. Chronic gamma ray irradiation may induce larger genetic changes compared with acute gamma ray irradiation. In addition, the transition/transversion ratio decreased as the dose rate increased, suggesting that plants responded to very low dose rates of gamma rays (~1 mGy/h), even though the overall mutation frequency did not increase. These data will aid our understanding of the effects of radiation types and be useful in selecting suitable radiation treatments for mutagenesis.